Recovery and Phylogenetic Analysis of nifH Sequences from Diazotrophic Bacteria Associated with Dead Aboveground Biomass of Spartina alterniflora - Lovell, Charles R. (American Society for Microbiology, 2001)
DNA was extracted from dry standing dead Spartina alterniflora stalks as well as dry Spartina wrack from the North Inlet (South Carolina) and Sapelo Island (Georgia) salt marshes. Partial nifH sequences were PCR amplified, the products were separated by denaturing gradient gel electrophoresis (DGGE), and the prominent DGGE bands were sequenced. Most sequences (109 of 121) clustered with those from α-Proteobacteria, and 4 were very similar (>99%) to that of Azospirillum brasilense. Seven sequences clustered with those from known γ-Proteobacteria and five with those from known anaerobic diazotrophs. The diazotroph assemblages associated with dead Spartina biomass in these two salt marshes were very similar, and relatively few major lineages were represented.